2014
DOI: 10.3852/13-007
|View full text |Cite
|
Sign up to set email alerts
|

Multigene phylogenetic analysis detects cryptic species ofTryblidiopsisin China

Abstract: Tryblidiopsis pinastri (Rhytismatales) has been recognized as being distributed throughout northern temperate regions. In the present study, comparative studies showed that species of Tryblidiopsis from China were distinct from the European type species. They are shown to belong to two new Tryblidiopsis species, T sichuanensis and T. sinensis, with a third known to be present in China but not described because the reference material is immature. Combined LSU rDNA, ITS rDNA and mtSSU rDNA sequences analyses rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…The detection of a novel Lophodermium species on an endemic North American host with a poorly characterized microbiota is expected given the recent descriptions of novel Lophodermium and D r a f t 16 other Rhytismataceae species worldwide (e.g. : Wang et al 2014;Koukol et al 2015;Masumoto et al 2015;Zhang et al 2015). Furthering our understanding of the biodiversity and taxonomy of Rhytismatales species will reveal insight into the coevolution of these fungi and their hosts, provide reference sequences facilitating the identification of sequences from endophyte and other ecological surveys, and potentially lead to the identification of novel bioactive secondary metabolites.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The detection of a novel Lophodermium species on an endemic North American host with a poorly characterized microbiota is expected given the recent descriptions of novel Lophodermium and D r a f t 16 other Rhytismataceae species worldwide (e.g. : Wang et al 2014;Koukol et al 2015;Masumoto et al 2015;Zhang et al 2015). Furthering our understanding of the biodiversity and taxonomy of Rhytismatales species will reveal insight into the coevolution of these fungi and their hosts, provide reference sequences facilitating the identification of sequences from endophyte and other ecological surveys, and potentially lead to the identification of novel bioactive secondary metabolites.…”
Section: Resultsmentioning
confidence: 99%
“…), Lophodermium macci(Sokolski et al 2004), and L. "piceae"(Stefani and Bérubé 2006a), while Chinese species of Lophodermium and Tryblidiopsis have also been distinguished from their European look-alikes(Gao et al 2013;Wang et al 2014). WhileOono et al (2014) suggested that all Pinus species can potentially host most Lophodermium species, this is unlikely given the polyphyly of Lophodermium and apparent narrow host preferences observed in other Rhytismataceae species, for example Lirula macrospora, Lophodermium piceae s.s., and Tryblidiopsis pinastri restricted to Picea abies(Lantz et al 2011; Tanney unpub data), Isthmiella faullii restricted to Abies balsamea(Darker 1932), Lophophacidium dooksii restricted to Pinus strobus(Corlett and Shoemaker 1984;Laflamme et al 2015), and Rhytisma salicinum and Cryptomyces maximus restricted to Salix(Lantz et al 2011).…”
mentioning
confidence: 99%
“…Tryblidiopsis diversity is probably still underestimated in both N. America and Asia, where host Picea species diversity is greater than in Europe. For example, Wang et al (2014) described two novel Tryblidiopsis species from Picea in China and also recognized a third novel species (Tryblidiopsis sp. HOU 662) based on an rDNA phylogeny, but declined to formally describe it because it was represented by only one collection of immature ascomata.…”
Section: Discussionmentioning
confidence: 99%
“…However, the delineation of a North American subspecies, T. pinastri subsp. americana, by Magnes (1997) and recent description of two Tryblidiopsis species from Picea in China (Wang et al 2014) demonstrate that the traditional morphotaxonomic concept of T. pinastri probably encompasses several species and suggests that the natural range of T. pinastri s. str. is restricted to Europe.…”
Section: Introductionmentioning
confidence: 99%